PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN TERHADAP MINAT PENGGUNAAN E-WALLET SHOPEEPAY - Farizzy Azwar Setia Putra; Netti Nurlenawati; Dexi Triadinda (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2023)
The purpose of this study is to determine the effect of perceived usefulness on intention to use and want to know how the effect of perceived ease of use on intention to use. This type of research is a verification research. The population of this study is Management Students class of 2019 at Buana Perjuangan University, Karawang who have used the ShopeePay E-wallet more than twice and the resulting number is 103 respondents. Sampling uses a quantitative approach and the technique of determining the sample is using a multistage random sampling technique, through two steps. In obtaining data and information that will support this research, the authors collect data by distributing questionnaires. The research results show that the ease of use of the ShopeePay E-wallet has a significant effect on interest in use. This can be seen from the statistical results which show the coefficient value obtained with an F-count value of 9.518 > F-table of 3.09 with a meaning of 0.000 <0.05, meaning visible convenience and convenience at the same time affect interest in using the ShopeePay E-wallet . The consequence of repeating respondents' reactions from the apparent usefulness factor, seeing the simplicity of interest in utilizing the ShopeePay E-wallet shows that the maximum total score is close to the scale range, namely 515.4 and shows the result of the total score, which is 495.0 (Strongly Agree). Thus each variable shows a positive attitude in using the ShopeePay E-wallet.